Uji daya hambat sediaan tetes telinga ekstrak daun â€œTebel-Tebelâ€ (Hoya carnosa) terhadap bakteri gram positif dan gram negatif penyebab Otitis Media Supuratif Kronik (OMSK) aktif tipe benigna secara in-vitro di RSUP Sanglah, Bali, Indonesia - I Wayan Lolik Lesmana; Eka Putra Setiawan; I Made Jawi (DiscoverSys Inc., 2020)
Background: The recent Chronic Suppurative Otitis Media (CSOM) management by antibiotic Chloramphenicol 1% ear drop seems to be ineffective due to the bacterial resistance, ototoxic effects, and the idiosyncratic response. Traditional medicine from Hoya carnosa leaf as ear drops has been suggested for alternative medicine because of its antibacterial properties. This study aims to evaluate the inhibition test of Hoya carnosa leaf-extract towards gram-positive and gram-negative bacteria causeMethods: An experimental study with a completely randomized post-test control group design has been conducted to the American Type Culture Collection (ATCC), which consists of Staphylococcus aureus, Streptococcus pyogenes, Pseudomonas aeruginosa dan Enterobacter spp. The Hoya carnosa leaf extract in-ear drop emulsion has been divided into 3 concentrations, such as 1%, 3%, and 5% w/v by simple random technique. As a positive control used Chloramphenicol 1% and as a negative control using 96% ethanol. Each treatment was repeated 5 times and data were analyzed by SPSS version 17 for Windows.Results: There was a significant difference in inhibitory diameter (IH) from ear drop dosage of (Hoya carnosa) leaf emulsions to Streptococcus pyogenes bacteria in concentrations of 3% and 5% (p<0.05). There was a significant difference from the inhibitory drug resistance (DDH) ear drop emulsion preparation leaf extract